Beneficial Performance Effects of Training Load Intensification Can Be Abolished by Functional Overreaching: Lessons From a Water Polo Study in Female Athletes - Brisola, Gabriel M.P. [UNESP]; Dutra, Yago M. [UNESP]; Murias, Juan M.; Zagatto, Alessandro M. [UNESP] (Wolters Kluwer, 2023)
Brisola, GMP, Dutra, YM, Murias, JM, and Zagatto, AM. Beneficial performance effects of training load intensification can be abolished by functional overreaching: Lessons from a water polo study in female athletes. J Strength Cond Res 37(6): e391-e402, 2023 - The purpose of this study was to compare the outcomes from 2 weeks of training load intensification strategy in female water polo players diagnosed with functional overreaching (F-OR) with no F-OR players (acute fatigue) on the performance outcomes and hormonal, immunological, and cardiac autonomic nervous system responses. Twenty-two female water polo players were allocated into control and intensification group during 7 weeks. The swimming performance, biochemical parameters, heart rate variability, profile of mood states, and upper respiratory tract infection symptoms were assessed twice before and twice after 2 weeks of intensification period. F-OR showed a worsening in total time of the repeated sprint ability (RSA) test compared with the control group and the acute fatigue group after intensification (p ≤ 0.035). Furthermore, after the tapering period, the F-OR group maintained worse total time of the RSA test than the acute fatigue group (p = 0.029). In addition, the acute fatigue group showed improvement in total time of the RSA test after intensification compared with the control group (p < 0.001). No significant interactions were found for the other parameters. Therefore, periods of intensification without the F-OR development can promote higher gains in the total time of the RSA test after intensification and tapering period.
Keywords: fatigue; high intensity; overload; supercompensation; tapering; team sport